Przełamanie oporu przeciwko zmianom w procesie wdrażania nowej strategii - Dylak, Małgorzata (Breaking resistance against changes in the process of implementation of the new strategy, 2006)
The paper presents the problem of the change and reluctance from workers’ side to novelties in the process of the implementation of a new strategy. Solutions to coming changes in workers’ preparation for the implementation of the strategy and breaking their resistance are presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 43-46